2003
DOI: 10.1046/j.1526-100x.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Restored Small Wetlands by Breeding Waterfowl in Prince Edward Island, Canada

Abstract: Since 1990 under the Eastern Habitat Joint Venture over 100 small wetlands have been restored in Prince Edward Island, Canada. Wetlands were restored by means of dredging accumulated sediment from erosion to emulate pre‐disturbance conditions (i.e., open water and extended hydroperiod). In 1998 and 1999 we compared waterfowl pair and brood use on 22 restored and 24 reference wetlands. More pairs and broods of Ring‐necked Ducks, Gadwall, Green‐winged Teal, and American Black Ducks used restored versus reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Such considerations would likely improve the regional enrollment process. Nonetheless, our results support the notion that basic, site-level conditions essential to wetland function and persistence should be the priority when restoring waterbird habitat through CREP (Stevens et al 2003). Investing in hydrologic planning and infrastructure to facilitate effective restoration and management, combined with monitoring compliance and development of site-specific restoration goals, should take precedence over concerns about location and landscape context.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Such considerations would likely improve the regional enrollment process. Nonetheless, our results support the notion that basic, site-level conditions essential to wetland function and persistence should be the priority when restoring waterbird habitat through CREP (Stevens et al 2003). Investing in hydrologic planning and infrastructure to facilitate effective restoration and management, combined with monitoring compliance and development of site-specific restoration goals, should take precedence over concerns about location and landscape context.…”
Section: Discussionsupporting
confidence: 69%
“…Distance to Illinois River (DIST). Waterbirds are believed to migrate in explicit geographic corridors that often follow major rivers (Bellrose 1980) and waterfowl species richness in restored wetlands may correlate positively with proximity to a river (Stevens et al 2003). Therefore, we included distance (km) of wetlands from the Illinois River in some models of migratory use and species richness of waterbirds.…”
Section: Analytical Approachmentioning
confidence: 99%
“…This structural complexity probably improved the suitability of the habitat for a greater variety of oldfield and grasslanddependent birds (Cutright et al 2006). Stevens et al (2003) reported higher use of scrub-shrub restored wetlands than of open grassland wetlands by Mallards, suggesting that woody cover may provide important visual isolation for Cutright et al (2006) list upland shrub or lowland shrub as the preferred habitat for many of the species that increased in abundance in our wetlands over the 10-year study period. In addition to increases in woody cover at the margins of these wetland restorations, cattail has expanded and become dense in much of what was formerly shallow open water (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The loss of many wetland-dependent waterfowl species from our study sites is likely due to a reduction in the amount of open water habitat available. Vegetation cover to open water ratio in small wetlands has been shown to affect bird richness, abundance, and community composition (Fairbairn and Dinsmore 2001;Stevens et al 2003, O'Neil et al 2008. Migrating birds use general landscape features to identify potential nesting and feeding habitats (Orians and Wittenberger 1991;Fairbairn and Dinsmore 2001), and waterfowl typically use restored wetlands as soon as they contain standing water (LaGrange and Dinsmore 1989, Sewell and Higgins 1991;Delphey and Dinsmore 1993).…”
Section: Discussionmentioning
confidence: 99%
“…We determined reproductive activity indirectly from observations of reproductive behavior including pairing, food and nest material carrying, and the presence of fledglings (sensu Vickery et al 1992;Gunn et al 2000;Doran et al 2005). Determining the relationship between point count data and reproductive indices is useful in light of the increased use of these indices in bird habitat studies (Vickery et al 1992;Dale et al 1997;Powell and Collier 1998;Martin and Morrison 1999;Rangen et al 2000;Cornell Lab of Ornithology 2003;Christoferson and Morrison 2001;Harris and Reed 2002;Stevens et al 2003). If point count data can effectively predict reproductive activity, the additional effort expended to collect reproductive activity data may be unnecessary.…”
mentioning
confidence: 99%